ANALISIS PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN KENDARAAN NIAGA MEREK HINO - Sari, Selvi Ita Purnama; Mirza, M (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
This research aims to examine and Analysis the Effect of Customer Relationship Management, Price Perception, and Quality of Service to Customer Loyalty Vehicle Logistic Brand Hino that became the object of research. The reaserch design used is quantitative and explanatory research type of survey methods. Data was collected using questionnaires to 105 respondents, the sampling technique used is online survey via customer emails as. The method of analysis is SPSS. The result of the research showed that customer relationship management has a positively and significant customer loyalty vehicle logistic, price perception have positiv and effect significant customer loyalty vehicle logistic, and quality of service positive and significant influence to customer loyalty vehicle logistic